A triple-mode hexa-standard reconfigurable TI cross-coupled ΣΔ modulator. Issue 7 (3rd July 2017) - Prakash A. V, Jos; Jose, Babita R.; Mathew, Jimson; Jose, Bijoy A.
ABSTRACT: Hardware reconfigurability is an attractive solution for modern multi-standard wireless systems. This paper analyses the performance and implementation of an efficient triple-mode hexa-standard reconfigurable sigma-delta (∑∆) modulator designed for six different wireless communication standards. Enhanced noise-shaping characteristics and increased digitisation rate, obtained by time-interleaved cross-coupling of ∑∆ paths, have been utilised for the modulator design. Power/hardware efficiency and the capability to acclimate the requirements of wide hexa-standard specifications are achieved by introducing an advanced noise-shaping structure, the dual-extended architecture. Simulation results of the proposed architecture using Hspice shows that the proposed modulator obtains a peak signal-to-noise ratio of 83.4/80.2/67.8/61.5/60.8/51.03 dB for hexa-standards, i.e. GSM​​​​​​​​/Bluetooth/GPS/WCDMA/WLAN/WiMAX standards with significantly less hardware and low operating frequency. The proposed architecture is implemented in 45 nm CMOS process using a 1 V supply and 0.7 V input range with a power consumption of 1.93 mW. Both architectural- and transistor-level simulation results prove the effectiveness and feasibility of this architecture to accomplish multi-standard cellular communication characteristics.